Wind Power Industry — information Modelling of Cooperation with Energy System - Kurzak, L. (Электронное моделирование, 2007)
This paper presents current status and perspectives of use of wind energy in the countries of Europe and the World. The problems connected with modelling and simulation of wind power plant operation and their cooperation with energy systems have been highlighted. The paper contains many statistical data which enabled to assess the opportunities of pure energy production. Описаны современное состояние и перспективы использования энергии ветра в странах Европы и в мире. Рассмотрены проблемы, связанные с моделированием работы станций, использующих энергию ветра, и их взаимодействие с энергетическими системами. Приведены статистические данные, позволяющие оценить возможности производства экологически чистой энергии. Описано сучасний стан та перспективи використання енергії вітру в країнах Європи і у світі. Розглянуто проблеми, пов’язані з моделюванням роботи станцій, що використовують енергію вітру, та їх взаємодію з енергетичними системами. Наведено статистичні дані, які дозволяют оцінювати можливості виробництва екологічно чистої энергії.